2010
DOI: 10.1093/ndt/gfq247
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a single dialysis session on spatial QRS-T angle in haemodialysis patients

Abstract: QRS-T is high in HD patients. HD enhances the inhomogeneities of action potential. Pre-dialysis QRS-T is mainly associated with troponin T elevation. HD-induced increase in QRS-T is mainly associated with potassium and SI changes. The possible clinical importance of the higher QRS-T in HD patients remains to be confirmed in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…In this study, we included 66 patients who had characteristics that are more close to the “real life” and besides the Tpe interval we evaluated the changes of the Tpe/QT ratio which seems to be the most reliable noninvasive electrocardiographic measure of spatial dispersion of repolarization. Interestingly, two recent studies assessed some other novel electrocardiographic indexes (QRS‐T angle and microvolt T‐wave alternans) and concluded that HD increases the heterogeneity of ventricular repolarization although the clinical importance of this phenomenon remains uncertain …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we included 66 patients who had characteristics that are more close to the “real life” and besides the Tpe interval we evaluated the changes of the Tpe/QT ratio which seems to be the most reliable noninvasive electrocardiographic measure of spatial dispersion of repolarization. Interestingly, two recent studies assessed some other novel electrocardiographic indexes (QRS‐T angle and microvolt T‐wave alternans) and concluded that HD increases the heterogeneity of ventricular repolarization although the clinical importance of this phenomenon remains uncertain …”
Section: Discussionmentioning
confidence: 99%
“…In fact, the T peak‐to‐end (Tpe) interval and the Tpe/QT ratio represent novel electrocardiographic indexes of arrhythmic risk that possibly correspond to the spatial dispersion of ventricular repolarization . Data on modern indexes of dispersion of repolarization in the dialysis population are sparse . Thus, in this study, we sought to investigate the effects of a single HD session on the aforementioned electrocardiographic indexes in patients with ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have validated the role of QRS/T angle (QRS/T) as a sensitive, powerful and independent risk stratifier for cardiac events in the general population [1][2][3] as well as in various clinical settings [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…41 FQRSTA is a very powerful predictor of cardiovascular events (e.g., myocardial ischemia), 42 sudden cardiac death, [13][14][15][16][17]43 appropriate ICD therapy, 44,45 all-cause mortality, 15,[33][34][35][36][37] increased cardiac-related hospitalizations, 17,35 reduced left ventricular function, [34][35][36]46 especially in patients with postinfarction, [13][14][15][16][17] acute myocardial infarction with LVEF ࣘ40%, 47 the elderly, 12 chronic dialysis, [18][19][20] heart failure with preserved ejection fraction, 17 and ischemic stroke 48 considered stronger than any of the classical cardiovascular risk factors. 16,17 Risk factors leading to an elevation in FQRSTA were related to coronary artery disease, dialysis, poor-controlled hypertension, 49,50 pulmonary arterial hypertension, 51 left/right ventricular hypertrophy, 51-54 dilated left ventricle, 55 lower LVEF, 56 DM, 57, 58 smoking, [57][58][59] and female gender.…”
Section: Dm and Fqrstamentioning
confidence: 99%
“…Recent reports showed that the maximal magnitude of frontal QRS-T angle (FQRSTA) was significantly associated with the prognosis of elderly patients, 12 myocardial infarction, [13][14][15][16][17] heart failure, 17 and chronic dialysis. [18][19][20] There was no report about the influence of DM on the virtual planar QRS vector, T vector, and FQRSTA, derived from a Holter monitor. In this study, we randomly enrolled several patients with and without type 2 DM (NDM) in order to exploit the influence of DM on planar QRS and T vector virtually derived from Holter.…”
mentioning
confidence: 99%